2013
DOI: 10.1111/cod.12016
|View full text |Cite
|
Sign up to set email alerts
|

Hairdressers presenting to an occupational dermatology clinic in Melbourne, Australia

Abstract: Multiple sensitizations and multiple factors contributing to OCD in hairdressers are common. More needs to be done to prevent the development of OCD in hairdressers in our geographical region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
65
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 42 publications
16
65
1
3
Order By: Relevance
“…We found, in agreement with another study [36], that hairdressers presented contact dermatitis, which was confirmed by dermatologists who performed patch tests. These tests revealed allergies to preservatives such as formaldehyde, fragrances, rubber chemicals, methyl-di-bromo-glutaronitrile in shampoos and to leave-on products.…”
Section: Discussionsupporting
confidence: 93%
“…We found, in agreement with another study [36], that hairdressers presented contact dermatitis, which was confirmed by dermatologists who performed patch tests. These tests revealed allergies to preservatives such as formaldehyde, fragrances, rubber chemicals, methyl-di-bromo-glutaronitrile in shampoos and to leave-on products.…”
Section: Discussionsupporting
confidence: 93%
“…Apprentices from Zagreb worked more with hair dyes than apprentices from Dalmatia, being consequently at higher risk for development of contact sensitization to components of hair dyes, mostly p ‐phenylenediamine (PPD), which is known as a potent occupational contact allergen in the hairdressing sector . This study did not address this issue, but it would be of interest to see in future studies how this difference in exposure is related to the occurrence of early sensitization to PPD in apprentices . Washing hands >20 times per day, which is considered to be a risk factor for skin irritation, was reported by more apprentices from Zagreb (28%, in comparison with 10% of apprentices from Dalmatia).…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is slightly higher than in the study conducted by Hillen et al [4], which found 3.2% of subjects to have contact scalp dermatitis caused by APS. APS is also a frequent occupational allergen in hairdressers [27,28,29,30]. …”
Section: Discussionmentioning
confidence: 99%